Family stories as resources for a decolonial culturally responsive pedagogy. Issue 5 (3rd September 2022) - Hickey-Moody, Anna; Horn, Christine
ABSTRACT: Engagement with family stories, religious and community practices can change a teacher's conception of thought. We propose teaching as thinking-with the world and teaching as thinking-with others . These terms draw on the philosophy of new materialist thinkers in expressing the ontological impacts of context and materiality. We explore the relationship between teaching and thinking as a distributed and engaged practice by investigating family stories as an avenue for teachers to pedagogically engage with student's lived experiences. We work with students as valued contributors to the learning environment, irrespective of academic achievements. We argue that engaging with family and faith stories as constitutional of thinking about, and doing, pedagogy can challenge the persistent racism. We are interested in experiential ways of knowing and modes of paying attention to the social and emotional learning that takes place as part of a pedagogic culture of care.